Long-term health consequences of avalanches in Iceland in 1995: A 16 year follow-up - Edda Björk Þórðardóttir 1980- (2016)
Background and aims: Mental health research has increasingly focused on the detrimental consequences of disasters on the health of survivors. However, to date, no study has investigated the effects of avalanches on survivor’s health beyond the first years. The aim of this thesis was to examine long-term health status of avalanche survivors 16 years after exposure. Furthermore, we aimed to assess potential risk factors for posttraumatic stress disorder (PTSD) symptoms among survivors in the long-term; particularly among those who were children at the time of the trauma. Materials and methods: Participants were 286 inhabitants of avalanche stricken towns (Sudavik and Flateyri) in the Westfjords of Iceland in 1995 (exposed group), irrespective of whether they were in or out of town at time of the avalanches and 357 residents of two towns in 1995 (Breiddalsvik and Raufarhofn) not geographically threatened by avalanches (unexposed group). Response rate for the avalanche survivors was 72% (286/399) and 66% (357/541) in the comparison group. Self-report questionnaires were sent in 2011 assessing background characteristics, disaster-related experiences and physical and mental health status. PTSD symptoms were assessed with the Posttraumatic Diagnostic Scale (PDS); sleep problems with the Pittsburgh Sleep Quality Index (PSQI) and PTSD-related sleep disruptions with the Pittsburgh Sleep Quality Index Addendum for PTSD (PSQI-A). Results: The avalanche and comparison groups where similar on all background characteristics. Results indicate that overall 16% of survivors experience current avalanche specific PTSD symptoms (PDS score > 14). In addition, compared to the non-exposed group, survivors present with increased risk of PTSD hyperarousal symptoms (>85th percentile) (adjusted relative risk [aRR] = 1.83; 98.3% confidence interval [CI] 1.23–2.74), musculoskeletal and nervous system problems (aRR 1.43; 99% CI 1.06–1.93) and gastrointestinal problems (aRR 2.16; 99% CI 1.21–3.86). Of sleep-related disturbances, we found ...